Probiotic fermented milk drink added with cashew pulp (Anacardium occidentale): formulation, physicochemical, microbiological and sensory characteristics (Research, Society and Development, 2020)
The health aspects associated with fermented milk products have resulted in increased consumption of this beverage. Three fermented beverages added with cashew pulp and different concentrations of whey (10, 20 and 30 %) were produced, being stored for a period of 28 days and evaluated regarding their physicochemical, microbiological and sensory characteristics. Fifty-two tasters evaluated acceptance of the beverages using hybrid 9-point hedonic scales. It was found that the lower the proportion of whey used in the beverages, the higher the total solids, proteins, fat and caloric values (p0.05). Beverages pH values did not differ when evaluated on the same day of storage (p>0.05). After 7, 14, 21 and 28 days of storage, differences were observed (p